Silver nanoparticles elevate mutagenesis of eukaryotic genomes - Kun Wu; Haichao Li; Yaohai Wang; Dan Liu; Hui Li; Yu Zhang; Michael Lynch; Hongan Long (G3: Genes, Genomes, Genetics, 2023)
AbstractMetal nanoparticles, especially silver, have been used in various medical scenarios, due to their excellent antimicrobial effects. Recent studies have shown that AgNPs do not exert mutagenic effects on target bacteria, but the degree to which they compromise eukaryotic genomes remains unclear. To study this, we evaluated the mutagenic effects of AgNPs on the fission yeast Schizosaccharomyces pombeS. pombe